The Effect of Business Assistance on Improving the Managerial Capacity of MSMEs in Banyumulek Village, Lombok Barat - Dony Hidayat; Lalu Adiyatma Taopikul Hadi; Junaidin (International Publisher (YAPENBI), 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a strategic sector in local economic development, particularly in rural areas. However, many MSME actors in Banyumulek Village, Lombok Barat, still face various obstacles in managerial aspects, such as business planning, financial recording, decision-making, and resource management. This study aims to analyze the effect of business mentoring on improving the managerial capacity of MSME actors in the village. The research method used is a quantitative method with a survey approach. The population in this study were all active MSME players in Banyumulek Village, and a purposive sample of 55 respondents was taken. Data collection techniques were conducted through questionnaires, interviews, and field observations. Data analysis was conducted using simple linear regression techniques to test the effect of business assistance variables on the managerial capacity of MSMEs. The results showed that business mentoring has a significant and positive effect on improving the managerial capacity of MSMEs. Most of the variation in managerial capacity building can be explained by the quality and intensity of mentoring received by businesses. Managerial aspects that experienced significant improvements included business planning, financial management, business evaluation, and human resource development. Assistance that is participatory, contextual, and oriented to real needs has proven to be more effective in encouraging managerial transformation of MSMEs. This study recommends the need to strengthen a sustainable mentoring system, involve multi-stakeholders, and integrate with digitalization training programs to support the growth of village MSMEs in a sustainable and adaptive manner to the challenges of modern markets.